The media's coverage of 'Closing the Gap' in Australian education. Issue 6 (1st November 2020) - Heffernan, Troy A.; Maxwell, Jacinta
ABSTRACT: Since 2007, 'Closing the Gap' between Indigenous and non-Indigenous people has been an ambition of Australian state and federal governments in areas including education, employment, and health. This paper examines media responses to government policies aimed at closing the achievement gap in schools. The paper analyses print and online newspaper articles in national and capital city/state-based newspapers that reported on the implementation and success of Closing the Gap policies in Australia's schools. The paper argues that media narratives are often based on NAPLAN results, data sourced from the MySchool website, or newspaper-created metrics that support their own narrative. This paper highlights the narratives being purported to readers via the selective nature of newspaper data, and subsequently how these narratives attempt to influence the public discourse.